How much does distance learning affect social life and psychology of growing adolescent - Teng, Ming Foey; Putra, Yudha Kusuma; Ilham, Muhammad; Pratama, Wahyu Arbianda Yudha (Association for Scientific Computing Electrical and Engineering, 2020)
Distance learning is one of the most important innovations in the education field. It provides flexibility when considering time and place in education while enhancing the efficiency of gathering knowledge. While distance learning improves the quality of education, distance learning diminishes the interaction between students and teachers or among students themselves. The lack of interaction that occurs in distance learning affects adolescent’s social life and psychology. In this research, we would like to study all the impacts that are going to affect students, especially in their social life and psychology. In this research, the method used is a document study or document analysis. The purpose of this research is to observe and analyze the impact of distance learning to improve distance learning in the future not only in educational but also in social and psychological side. With this research, we find that students that use distance learning without any interaction with the others tend to induce an antisocial behavior which leads to loneliness and suicidal thought.